2017
DOI: 10.1016/j.ijsu.2016.12.119
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with blunt liver or spleen injuries: Experience from a single institution in Korea

Abstract: Our data demonstrated that 85.7% of patients with spleen injuries and 88.2% of patients with liver injuries were managed nonoperatively. Operative management was chosen more selectively, being applied in patients with high grade organ injury scores or abrupt changes in vital status. Our findings will contribute to the available data concerning children with traumatic injuries in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
3
1
0
1
Order By: Relevance
“…Similarly to our findings, a study on admissions of 6,577 MLCs to the pediatric emergency unit revealed that blunt or sharp force injuries were most frequently seen in the age group of 14.5 to 18 years (10). Blunt trauma constitutes the majority of pediatric traumas (11). In the USA, it has been reported that nearly half a million children under the age of fourteen experience traumatic brain injuries annually, with 90% of them being discharged with minor injuries, but nearly three thousand children do not survive (12).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to our findings, a study on admissions of 6,577 MLCs to the pediatric emergency unit revealed that blunt or sharp force injuries were most frequently seen in the age group of 14.5 to 18 years (10). Blunt trauma constitutes the majority of pediatric traumas (11). In the USA, it has been reported that nearly half a million children under the age of fourteen experience traumatic brain injuries annually, with 90% of them being discharged with minor injuries, but nearly three thousand children do not survive (12).…”
Section: Discussionsupporting
confidence: 87%
“…A relatively low percentage of patients who underwent a splenectomy (6.2%) was found in relation to comparable international studies (1,13,20,(30)(31)(32)(33)(34)(35)(36)(37)(38) (Supplementary Table 3) and studies performed in the Netherlands, in which 17.4% and 21.3% of patients underwent a splenectomy, respectively (16,39). This study supports that unstable hemodynamics is an independent risk factor for splenectomy in children (5), possibly in combination with the presence of an active blush on the CT scan.…”
Section: Managementsupporting
confidence: 63%
“…In the present study, none of the patients who were followed up without surgery had no delayed surgical requirements. Recent studies have reported that the success rate of non-surgical follow-up in patients with high-grade liver injuries is between 60-70% (20,21). In the present study, for 4 patients with Grade IV injuries, non-surgical follow up was achieved at the rate of 50%.…”
Section: Discussionsupporting
confidence: 46%